(untitled) (Mongolian Journal of International Affairs, 2025)
The Shanghai Cooperation Organization (SCO) has evolved as a regionally important and internationally attractive regional organization. Albeit its inherent challenges of dealing with competitive interests of great powers, regional powers, and Central Asia states, the SCO has become well institutionalized as an organization, endured during the global pandemics and geopolitical tensions, and kept its focus on Central Asia. Mongolia had been welcomed by its two powerful members, China and Russia, to become a full member of the organization, but this invitation was not uniformly endorsed by Mongolian political leaders, pundits, and even the public. This resulted in an observer status. However, last September, the SCO merged both observer and partner statuses - ending Mongolia’s unique status of the observer. This article argues a key reason for Mongolia’s hesitance in joining the SCO is its explicit regional identification with East Asia, not Central Asia. We will discuss Mongolia’s involvement during different phases of the organizational evolution, analyze the internal debate about the country’s membership, and present our explanation of contemporary Mongolia’s identification with the East Asian region.